The impacts of public expenditure innovations on real effective exchange rate volatility in South Africa - Naser Yenus Nuru; Hayelom Yrgaw Gereziher (Cogent Economics & Finance, 2025)
This study examines the impacts of public expenditure innovations on exchange rate volatility in South Africa, utilizing quarterly data from 1970 to 2019. To achieve this objective, a vector autoregressive impulse response model variant, proposed by Jordà, is employed, with innovations identified recursively. The impulse response functions reveal that public expenditure innovation has a decreasing but insignificant impact on exchange rate volatility, and its impact depends on the type of fiscal expenditure innovation. While the impact of public expenditure innovation on exchange rate volatility does not depend on the direction of the innovation, it varies according to the state of the economy. Public expenditure innovation reduces exchange rate volatility during economic upturns but tends to increase it during downturns. Additionally, the size of the impact is greater during upturns than downturns.